Survey of multi-agent systems for microgrid control. (October 2015) - Kantamneni, Abhilash; Brown, Laura E.; Parker, Gordon; Weaver, Wayne W.
Abstract: Multi-agent systems (MAS) consist of multiple intelligent agents that interact to solve problems that may be beyond the capabilities of a single agent or system. For many years, conceptual MAS designs and architectures have been proposed for applications in power systems and power engineering. With the increasing use and modeling of distributed energy resources for microgrid applications, MAS are well suited to manage the size and complexity of these energy systems. The purpose of this paper is to survey applications of MAS in the control and operation of microgrids. The paper will review MAS concepts, architectures, develop platforms and processes, provide example applications, and discuss limitations.